Seducing the voters the powerful and limited effects of TV electioneering - Portus, Lourdes M. (2008)
This study focuses on television (TV)'s seduction of selected Metro Manila voters into electing TV personalities. It explores the influence of TV and other factors on the electorate's voting behavior. Citing the senatorial and mayoral elections of May 2001 as cases, the study interviewed 121 households and eight personalities from media and the academe. Using the Agenda-Setting and Limited Effects Theories, the study reveals that TV could have been a powerful tool in shaping voters' behavior. The influencing factors include length of TV exposure and image packaging of candidates. However, there are other qualifications like educational attainment, past accomplishments, and good reputation that voters consider in a candidate. Hence, to emerge victorious in elections, a candidate needs much more than mere presence in TV programs. The study also indicates that certain personalities deliberately use TV in anticipation of elections. This explains the incessant campaign or electioneering embedded in so-called "service programs," "talk shows," "infomercials," and other TV projects - months before the election season begins. This also affirms the notion that an extended and prolonged TV exposure enhances name-recall in voters - a possible winning edge for politicians.
Includes bibliographical references (pages 23-24).
Keywords: Elections